2004
DOI: 10.4049/jimmunol.172.4.2678
|View full text |Cite
|
Sign up to set email alerts
|

CD40 Ligand Dysregulation in HIV Infection: HIV Glycoprotein 120 Inhibits Signaling Cascades Upstream of CD40 Ligand Transcription

Abstract: IL-12 production and up-regulation of CD40 ligand (CD40L) expression are impaired in the PBMC of HIV-infected donors, and exogenous CD40L rescues IL-12 production by such cells. In this study, we implicate dysregulation of CD40L expression in the IL-12 defect associated with HIV by demonstrating that induction of CD40L expression by anti-CD3/CD28 stimulation was directly correlated with the IL-12 productive capacity of PBMC. Further, we demonstrate marked decreases in the induction of CD40L protein and mRNA fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 69 publications
3
55
0
Order By: Relevance
“…CD154 is the cognate ligand for CD40 and is principally expressed on activated T cells. FIV infection markedly increased CD154 expression on T cells both in vivo and in vitro, similar to that observed in HIV infection (Zhang et al, 2004), although PMA decreased the CD154 expression on uninfected T cells, including CD4ϩ and CD8ϩ T cells in vitro, which was correlated with the degree of neuronal injury. Functional blockage of CD154 expression on CD8 T cells significantly attenuated the neuronal injury induced by FIV-infected and uninfected CD8ϩ T cells in terms of neurite length and soma size, indicating that engagement of CD40 expressed on neurons by CD154 expressed by CD8ϩ T cells caused DRG neuronal injury.…”
Section: Discussionsupporting
confidence: 70%
“…CD154 is the cognate ligand for CD40 and is principally expressed on activated T cells. FIV infection markedly increased CD154 expression on T cells both in vivo and in vitro, similar to that observed in HIV infection (Zhang et al, 2004), although PMA decreased the CD154 expression on uninfected T cells, including CD4ϩ and CD8ϩ T cells in vitro, which was correlated with the degree of neuronal injury. Functional blockage of CD154 expression on CD8 T cells significantly attenuated the neuronal injury induced by FIV-infected and uninfected CD8ϩ T cells in terms of neurite length and soma size, indicating that engagement of CD40 expressed on neurons by CD154 expressed by CD8ϩ T cells caused DRG neuronal injury.…”
Section: Discussionsupporting
confidence: 70%
“…The clinical relevance of CD154 as well as its central role as a regulator of cell-mediated and humoral immunity led to studies that examined whether induction of CD154 is defective in CD4 ϩ T cells from HIV-1 ϩ patients. Although there are reports that HIV-1 infection is accompanied by defective CD154 induction upon T cell activation (13)(14)(15)(16)(17)(18), other studies did not find evidence of this defect (19,20). A common feature of the studies that reported a normal induction of CD154 in CD4 ϩ T cells from HIV-1 ϩ patients is that T cell activation was induced in the absence of CD40 ϩ APC (19,20).…”
Section: T He Interaction Between T Cells and Apcs Is An Event Centramentioning
confidence: 99%
“…After treatment with DNase (Ambion), 0.5 g of RNA was used to generate cDNA using oligo(dT) [12][13][14][15][16][17][18] primers and Superscript III reverse transcriptase (Invitrogen Life Technologies). cDNA was subjected to RT-PCR using the LightCycler SYBR green fluorophore.…”
Section: Cd4mentioning
confidence: 99%
See 1 more Smart Citation
“…Impaired CD154 induction is particularly more pronounced in preterm babies (Kaur et al 2007), a finding relevant to toxoplasmosis in newborns since this is an infection acquired prior to birth. The CD40-dependent pathway of host protection is also relevant to HIV-1 + patients because these individuals exhibit a defect in CD154 induction in their CD4 + T cells (Subauste et al 2001, 2007b, Zhang et al 2004.…”
Section: Potential Relevance Of Cd40-induced Autophagy In T Gondii Imentioning
confidence: 99%